(untitled) (Research, Society and Development, 2022)
Introduction: Physical exercise is important for people’s health maintenance, what is unknown to some people is that the regular practice of physical exercise is a determining factor in the treatment of several pathologies including type I and II diabetes mellitus. Diabetes is an endocrine disease characterized by high levels of blood glucose (hyperglycemia), such a situation can generate imbalances and consequent damage to tissues and vital organs. Objective: to demonstrate the benefits that physical exercise brings to glycemic control in patients with type I and II diabetes mellitus. Proposed methodology: This work is an integrative literature review, carried out through research on scientific articles present in traditional databases of health knowledge such as: PubMed, SciELO, Science Direct, CAPES, between 2015 and 2021. Results and discussion: we see that the practice of physical exercises is crucial in all processes of body homeostasis and contributes directly to minimize the effects resulting from conditions involving diabetes, and the importance of the pharmacist in health care. Conclusion: Due to the high incidence of diabetes in the context of global health, it is important to emphasize that physical activity is essential for health, pharmaceutical assistance has also been gaining prominence for diabetics to remain healthy.